Economics - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
Research in bean economics includes production, marketing and consumption, and policy studies. Production research focuses on 2 mutually reinforcing themes: (1) assessment of the spread of new var. recently released to farmers by national programs; and (2) assessment of farmers' current production systems and problems. Consumption and marketing of beans remain important research topics because most beans in Latin America are produced for the market, thus making consumer acceptability, price, and ease of market entry, critical factors in determining farmer adoption of new bean var. Case studies of policies affecting bean production and markets are undertaken when they have an important impact on the environment for which the new technology is being developed. A great deal of the research on all these issues is conducted in collaboration with national programs. Strengthening their research capacity through training and collaborative projects is an important activity. (AS)